2019
DOI: 10.1097/md.0000000000016176
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of pulsed low-dose rate radiotherapy for local recurrent esophageal squamous cell carcinoma after radiotherapy

Abstract: Introduction: Re-irradiation after radiotherapy is a common treatment for locally recurrent esophageal cancer. However, the side effects of re-irradiation are serious. The most serious adverse reactions of re-irradiation include esophageal perforation and hemorrhage caused by esophageal perforation. Studies have shown that pulsed low-dose rate radiotherapy (PLDR) induces a hypersensitivity effect on tumor tissue and a hyper-repair effect on normal tissue, which can simultaneously reduce damage on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…The use of PLDR irradiation in local recurrent HNSCC has been recently tested in a clinical trial in order to evaluate safety and treatment efficacy. [31][32][33] PLDR irradiation was initially proposed for the treatment of recurrent radioresistant gliomas. 13,16 It exploits two phenomena, LDHRS, and the inverse dose-rate effect.…”
Section: Discussionmentioning
confidence: 99%
“…The use of PLDR irradiation in local recurrent HNSCC has been recently tested in a clinical trial in order to evaluate safety and treatment efficacy. [31][32][33] PLDR irradiation was initially proposed for the treatment of recurrent radioresistant gliomas. 13,16 It exploits two phenomena, LDHRS, and the inverse dose-rate effect.…”
Section: Discussionmentioning
confidence: 99%
“…7 However, the serious side effects and unexpected risks are not uncommon, including esophageal perforation, hemorrhage, dysphagia. 8,9 Therefore, exploring the promising therapeutic molecular targets may help to understand the diagnosis and treatment of EC.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation strategy for PLDR involves dividing 2.00 Gy into ten fractions and administering each irradiating dose of 20 cGy at an interval of 3 min before the next low-dose radiation (Li et al, 2019). The pulse dose is within the dose range for tumor radiosensitivity and normal tissue radioresistance, which can contribute to a higher rate of tumor cell apoptosis while better protecting normal tissues from radiation damage.…”
mentioning
confidence: 99%
“…The pulse dose is within the dose range for tumor radiosensitivity and normal tissue radioresistance, which can contribute to a higher rate of tumor cell apoptosis while better protecting normal tissues from radiation damage. Relevant basic and clinical studies have shown that PLDR improves the local control rate and the quality of life of cancer patients (Li et al, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation